SOSTAC sebagai Strategi Pemasaran Digital pada Start-Up Picnicker untuk Meningkatkan Merchant - Indana Nazulfa; Rudi Santoso (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
This study examines and reveals that digital marketing strategies using SOSTAC are more effectively applied to startups during the post-pandemic compared to strategies that are already mainstream. The novelty of this research lies in the application of the SOSTAC strategy for start-up businesses. The research method used is SOSTAC or short for Situation Analysis, Objective, Strategy, Tactic, Action, and Controlling. In the early days before implementing SOSTAC, the startup had difficulty increasing merchants. Even though the number of merchants who join this startup is one indication of the success of the business. The Key Performance Indicators used are 12 digital marketing dimensions plus 1 target increase in merchants. The results showed a significant increase in each component of the indicators used. Performance improvement based on the smallest percentage is 14% and the highest is 500%. This study at the same time reinforces previous research that the application of SOSTAC is more effective when compared to using the usual strategy.